Effectiveness and Contribution of Hotel Tax to Regional Income of Badung Regency - Rosadi, Farra Shayrani; Munawaroh, Inas Suryani; Wicaksono, Galih; Huda, Muhammad Nasrulloh (ARBITRASE: Journal of Economics and Accounting, 2023)
According to Law Number 1 of 2022 concering Financial Relations between the Central Goverment and Regional Goverments, Local Own Revenue is regional taxes, regional levies, result of separated regional wealth management, and other legal regional original revenues in accordance with statutory regulations. The central goverment gives authority to regional goverments to regulate their respective regional PAD, so that regional goverments must be able to explore potential revenues in their areas. Hotel tax is a type pf regional tax that has the potential to provide income to PAD which can spur economic development in Badung Regency. The purpose of this study was to determine the effectiveness and contribution of hotel tax to local revenue. The method used in this research is descriptive quantitative. This study took secondary data contained in the website managed bt the Badung Regency Regional Revenue Agency (Bapenda). The result of this study indicate that the effectiveness in the 2019-2021, as well as its contribution to PAD is still in the less category.